Hippocampal Connectivity of the Presubiculum in the Common Marmoset (Callithrix jacchus) - Honda, Yoshiko; Shimokawa, Tetsuya; Matsuda, Seiji; Kobayashi, Yasushi; Moriya-Ito, Keiko (Frontiers in Neural Circuits, 2022)
We previously investigated hippocampal-parahippocampal connections in rats and rabbits and found that some features of connectivity differed between species. Unlike that in rats, the rabbit presubiculum received abundant input directly from CA1 pyramidal cells and had many reciprocal connections with the superficial layers of the entorhinal cortex. These results highlighted the need for a detailed comparative analysis of hippocampal-parahippocampal connections in primates and other animal species. While the marmoset, a New World monkey, has recently received attention as an experimental animal model, little is known about the connectivity of its limbic regions, including cortical and hippocampal memory circuits. Thus, we investigated the neuronal connectivity of the marmoset, focusing on the connectivity between the hippocampal formation and the presubiculum, using retrograde and anterograde tracers (cholera toxin B subunit and biotin dextran amine). We demonstrated the presence of a direct projection from the CA1 pyramidal cell layer to the deep layers of the presubiculum in the marmoset, which was previously identified in the rabbit but not in the rat or other non-human primates. We also found that the cells of origin of subiculo-presubicular projections were localized in the middle part along the superficial-to-deep axis of the pyramidal cell layer of the distal subiculum in the marmoset, similar to that in both rats and rabbits. Our results suggest that compared to rat and rabbit brains, connections between the hippocampal formation and presubiculum are highly organized and characteristic in the marmoset brain.